Using two dyes to observe the competition of Ca2+ trapping mechanisms and their effect on intracellular Ca2+ signals - Piegari, Estefanía (2018)
The specificity and universality of intracellular Ca2+ signals rely on the variety of spatio-temporal patterns that the Ca2+ concentration can display. Ca2+ liberation through inositol 1,4,5-trisphosphate receptors (IP3Rs) is key for this variety. In this paper, we study how the competition between buffers of different kinetics affects Ca2+ signals that involve Ca2+ release through IP3Rs. The study also provides insight into the underlying spatial distribution of the channels that participate in the signals. Previous works on the effects of Ca2+ buffers have drawn conclusions 'indirectly' by observing the Ca2+-bound dye distributions in the presence of varying concentrations of exogenous buffers and using simulations to interpret the results. In this paper, we make visible the invisible by observing the signals simultaneously with two dyes, Rhod-2 and Fluo-4, each of which plays the role of a slow or fast Ca2+ buffer, respectively. Our observations obtained for different concentrations of Fluo-4 highlight the dual role that fast buffers exert on the dynamics, either reducing the intracluster channel coupling or preventing channel inhibition and allowing the occurrence of relatively long cycles of Ca2+ release. Our experiments also show that signals with relatively high Ca2+ release rates remain localized in the presence of large Rhod-2 concentrations, while the mean speed of the elicited waves increases. We interpret this as a consequence of the more effective uncoupling between IP3R clusters as the slow dye concentration increases. Combining the analysis of the experiments with numerical simulations, we also conclude that Ca2+ release not only occurs within the close vicinity of the centers of the clearly identifiable release sites (IP3R clusters) but there are also functional IP3Rs in between them.